2020
DOI: 10.5430/ijfr.v11n3p106
|View full text |Cite
|
Sign up to set email alerts
|

Credit Risk, Islamic Contracts and Ownership Status: Evidence From Malaysian Islamic Banks

Abstract: The paper attempts to model the key drivers of credit risk for Islamic banks in Malaysia. This paper is motivated to introduce Islamic financing types (IFT) and banks ownership status (STATUS) as additional factors in investigating the key drivers. This study also investigates the level of credit risk between the crisis and non-crisis period. This study employs a panel data analysis method using generalized least squares (GLS) regression for random effect model. The dependent variable is credit risk which assu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 19 publications
(27 reference statements)
0
0
0
Order By: Relevance
“…At country-level, the use of LLPs for earnings management/ smoothing are found by Alali andJaggi (2011), El Sood (2012), Dolar (2016Dolar ( ), P erez et al (2008, AJEB Carbo-Valverde and Rodriguez-Fernandez (2018), Pinho and Martins (2009), Curcio et al (2014) and Nikulin and Downing (2021). More evidence of the use of LLPs for earnings smoothing/management is also identifiable with findings of Abdullah et al (2013), Adzis et al (2015), Misman and Ahmad (2011), Chang et al (2008), Floro (2010, Skała (2014), Fernando and Ekanayake (2015), Acar and Ipci (2015), Dushku (2016), Schechtman and Takeda (2018), Muriu and Josea (2020), Le et al (2021) and Pandey et al (2022). For cross-country studies, the empirical findings of positive relationship between LLPs and EBTL, are traceable to the works of Hasan and Wall (2004), Zoubi and Al-Khazali (2007), Fonseca and Gonz alez (2008), Bouvatier and Lepetit (2012), Bushman and Williams (2012), Olson and Zoubi (2014), Curcio and Hasan (2015), Abdullah et al (2017), Elnahass et al (2018), Skała (2018), Zainuldin and Lui (2020), Doan et al (2020) and Ozili (2022a).…”
Section: Previous Empirical Findings and Hypotheses Developmentmentioning
confidence: 85%
See 2 more Smart Citations
“…At country-level, the use of LLPs for earnings management/ smoothing are found by Alali andJaggi (2011), El Sood (2012), Dolar (2016Dolar ( ), P erez et al (2008, AJEB Carbo-Valverde and Rodriguez-Fernandez (2018), Pinho and Martins (2009), Curcio et al (2014) and Nikulin and Downing (2021). More evidence of the use of LLPs for earnings smoothing/management is also identifiable with findings of Abdullah et al (2013), Adzis et al (2015), Misman and Ahmad (2011), Chang et al (2008), Floro (2010, Skała (2014), Fernando and Ekanayake (2015), Acar and Ipci (2015), Dushku (2016), Schechtman and Takeda (2018), Muriu and Josea (2020), Le et al (2021) and Pandey et al (2022). For cross-country studies, the empirical findings of positive relationship between LLPs and EBTL, are traceable to the works of Hasan and Wall (2004), Zoubi and Al-Khazali (2007), Fonseca and Gonz alez (2008), Bouvatier and Lepetit (2012), Bushman and Williams (2012), Olson and Zoubi (2014), Curcio and Hasan (2015), Abdullah et al (2017), Elnahass et al (2018), Skała (2018), Zainuldin and Lui (2020), Doan et al (2020) and Ozili (2022a).…”
Section: Previous Empirical Findings and Hypotheses Developmentmentioning
confidence: 85%
“…There is more empirical evidence of the use of LLPs to manage capital in the literature (Ahmed et al, 1999;Anandarajan et al, 2003Anandarajan et al, , 2005Kanagaretnam et al, 2004;Alali andJaggi, 2011 andTran et al, 2020). Other studies with evidence of capital management include Anandarajan et al (2007), Ghosh (2007), Kwak et al (2009), Pinho and Martins (2009), Floro (2010), Misman and Ahmad (2011), Karimiyana et al (2014), Schechtman and Takeda (2018) and Muriu and Josea (2020). At cross-country level, Bouvatier and Lepetit (2012), Ben Othman and Mersni ( 2014) and Curcio and Hasan (2015), found the use of LLPs for capital management.…”
Section: Previous Empirical Findings and Hypotheses Developmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Grassa (2012), using a sample of IBs in the GCC countries, concluded that greater revenue sharing leads to higher levels of risk for IBs. Thus, IBs with high EBF tend to have higher credit risks (Khan & Ahmed, 2001;Ariffin et al, 2009;Misman et al, 2020). In addition, the high credit risk in EBF may be due to agency problems (Dar & Presley, 2000;Beck et al, 2013); information asymmetry (Muda & Ismail, 2010;Warninda et al, 2019); and moral hazard (Mahmood & Rahman, 2017).…”
Section: Hypothesis Developmentmentioning
confidence: 99%
“…Past literature highlighted that the global Islamic banking industry has EBF ratios which are less dominant than debt-based financing (DBF) ratios (Mills & Presley, 1999;Siddiqui, 2008;Anisykurlillah et al, 2018;Warninda et al, 2019;Miah & Suzuki, 2020). Data on the EBF ratio of the global Islamic banking industry are depicted in Table 1.…”
Section: Introductionmentioning
confidence: 99%